2005
DOI: 10.1111/j.1365-2516.2005.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of factor XI inhibitor using recombinant activated factor VIIa

Abstract: A 30-year-old female with severe factor XI deficiency of 0-2% acquired factor XI inhibitor following many infusions for fresh frozen plasma (FFP) for surgical procedures starting at 4 years of age. Seven months before this inhibitor was diagnosed, surgery was complicated by prolonged bleeding resistant to FFP, requiring epsilon aminocaproic acid (EACA) and surgical packing. The inhibitor was measured at 2.2 Bethesda units, 7 months since the last FFP. The inhibitor was confirmed as specific anti-XI and anti-XI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…The management of FXI(À) patients remains controversial; however, rFVIIa [22,23] and antifibrinolytic agents [24,25] have been used instead of plasma exchange/transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The management of FXI(À) patients remains controversial; however, rFVIIa [22,23] and antifibrinolytic agents [24,25] have been used instead of plasma exchange/transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Experimental work has shown that a lower amount of rVIIa is required for thrombin generation in FXI-deficient plasma than in severe hemophilia A or B plasmas. 36 Use of lower doses of rVIIa (15-20 μg/kg) may reduce the risk of thrombosis observed in a series of patients treated for surgery where the conventional dose of 90 μg/kg was used.…”
Section: Clinical Presentation and Managementmentioning
confidence: 99%
“…As for all blood products there are concerns about the risk of transfusion-transmitted infections. Recombinant factor VIIa (rFVIIa) has been used successfully in these patients [92][93][94], although it is as yet unlicensed in this setting. Its short half-life makes it unsuitable for use to cover labour, but could be used for management of elective caesarean section.…”
Section: Factor XI Deficiencymentioning
confidence: 99%